2013
DOI: 10.1111/anec.12077
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Surface ECG Was a Poor Predictor of Appropriate Therapies in Patients with Chagas’ Cardiomyopathy and ICD Implantation (Fragmented ECG in CHAgas’ Cardiomyopathy Study)

Abstract: fQRS is highly prevalent among patients with CChC. It has been found a poor predictor of appropriate therapies delivered by the ICD in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…The presence of premature ventricular contractions, increased QT-interval dispersion, low-voltage QRS, QRS fragmentation, and prolonged QRS duration have all been associated with a worse prognosis. [38][39][40] Once ECG abnormalities arise, they imply disease progression (stage B; Table 1), preceding the appearance of HF symptoms (stages C and D). ECG abnormalities are frequent and related primarily with nonspecific repolarization alterations (30%-40%), right bundle branch block in conjunction with left anterior fascicular block (20%-35%), premature ventricular ectopic beats (5%-10%), and atrial fibrillation (5%-10%).…”
Section: Iva Electrocardiography and Continuous Rhythm Monitoringmentioning
confidence: 99%
“…The presence of premature ventricular contractions, increased QT-interval dispersion, low-voltage QRS, QRS fragmentation, and prolonged QRS duration have all been associated with a worse prognosis. [38][39][40] Once ECG abnormalities arise, they imply disease progression (stage B; Table 1), preceding the appearance of HF symptoms (stages C and D). ECG abnormalities are frequent and related primarily with nonspecific repolarization alterations (30%-40%), right bundle branch block in conjunction with left anterior fascicular block (20%-35%), premature ventricular ectopic beats (5%-10%), and atrial fibrillation (5%-10%).…”
Section: Iva Electrocardiography and Continuous Rhythm Monitoringmentioning
confidence: 99%
“…There are several reports that show correlation between fQRS and other cardiac diseases [16] such as ventricular arrhythmias and idiopathic ventricular fibrillation [18], Brugada and acquired long QT syndromes [19], and a variety of structural heart diseases such as idiopathic dilated and hypertrophic cardiomyopathies [20], Chagas' cardiomyopathy [21], and miscellaneous diseases such as Behcet's disease [22] and sarcoidosis [23]. Also, some studies reported fQRS as a normal LR -likelihood ratio; DOR -diagnostic odds ratio variant in the elderly population [24], who are a significant part of suspected CAD patients.…”
Section: Fragmented Qrs Specificitymentioning
confidence: 99%
“…21 Our group studied patients with ChCM and ICD with the aim to evaluate the role of fQRS as a marker of arrhythmias. 22 We included 98 patients from 14 centers in Latin America; the mean follow up was 33±20 months. fQRS was found in 56 of the patients (59.6%).…”
Section: Ecg Markersmentioning
confidence: 99%